2015
DOI: 10.1161/strokeaha.115.009013
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Variation in Carotid Artery Revascularization Utilization and Outcomes

Abstract: Background and Purpose— It is not known whether racial or ethnic disparities observed with other revascularization procedures are also seen with carotid artery stenting (CAS) and endarterectomy (CEA). Methods— We compared the utilization and outcomes of CAS and CEA across racial/ethnic groups within the CARE Registry between May 2007 and December 2012. Results— Between 2007 and 2012, of the 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…This racial disparity may reflect an underlying difference in socioeconomic factors, which have been shown to be associated with delayed access to healthcare. [19][20][21] Baseline comorbidities in patients who underwent carotid revascularization showed some distinctions between patients who underwent CEA vs CAS. The majority of patients understudy were hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…This racial disparity may reflect an underlying difference in socioeconomic factors, which have been shown to be associated with delayed access to healthcare. [19][20][21] Baseline comorbidities in patients who underwent carotid revascularization showed some distinctions between patients who underwent CEA vs CAS. The majority of patients understudy were hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 However, more worrisome, they differed in their identified effect of race on outcomes after CEA, as two found no association between race and stroke or death, 8,21 whereas one did find an association between Black race and 30-day mortality. 18 Despite comparable perioperative complication rates between Black and White patients in our study, Black patients experienced longer LOS and more failed discharges to home, which might reflect differences in socioeconomic factors and social networks, in combination with their overall higher disease burden.…”
Section: Discussionmentioning
confidence: 56%
“…Overall, most were limited by a small sample of Black patients, with very small event numbers. 5,6,8,17,18 Additionally, those using administrative or Medicare data lacked information on preprocedural stroke or TIA laterality, impeding a reliable classification of symptomatic patients. 5,7,9 This could result in biased racial comparisons among CEA patients, as Black patients are more likely symptomatic and more often have an ipsilateral stroke as their presenting symptom.…”
Section: Discussionmentioning
confidence: 99%
“…18, 19 For carotid artery stenting (CAS), the CARE Registry showed that the risk of perioperative stroke did not differ by race for CAS, though the risk for stroke or major adverse cardiac or cerebrovascular events was significantly higher in blacks for CEA. 20…”
Section: Background and Purposementioning
confidence: 99%